2021
DOI: 10.1155/2021/8065868
|View full text |Cite|
|
Sign up to set email alerts
|

Intervention Effect of Rapid Rehabilitation Nursing Combined with Continuous Nursing after Discharge on Patients with Cerebral Infarction in Recovery Period and the Changes in Motor Function, Mental State, and Quality of Life

Abstract: Objective. To explore the effect of rapid rehabilitation nursing combined with continuous nursing after discharge on patients with cerebral infarction (CI) in recovery period and its influence on motor function, mental state, and quality of life. Methods. From January 2018 to December 2020, 136 patients with CI in recovery period were selected and randomly divided into control group (n = 68) and observation group (n = 68). The control group was given routine nursing, and the observation group was given rapid r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
13
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 20 publications
1
13
0
Order By: Relevance
“…This study also found faster and more efficient elimination of psychological anxiety and depression in OG. Xie et al [35] reported that the NEs of patients with cerebral infarction were significantly alleviated after ERAS combined with continuous nursing, which is consistent with our findings. In the recovery of various diseases, NEs will not only weaken the recovery effect of patients but also aggravate their illness.…”
Section: Discussionsupporting
confidence: 92%
“…This study also found faster and more efficient elimination of psychological anxiety and depression in OG. Xie et al [35] reported that the NEs of patients with cerebral infarction were significantly alleviated after ERAS combined with continuous nursing, which is consistent with our findings. In the recovery of various diseases, NEs will not only weaken the recovery effect of patients but also aggravate their illness.…”
Section: Discussionsupporting
confidence: 92%
“…Of the 13 studies included in the review, 6 of them included the role of the occupational therapist and were conducted in Denmark, Sweden, Germany, Norway, and South Africa, highlighting the resurgent importance of occupational therapy in Northern European countries [ 42 , 43 , 44 , 45 , 46 , 47 ]. However, of the seven included studies that did not name OT, six of them were conducted in China [ 48 , 49 , 50 , 51 , 52 , 53 ] and one in Australia [ 54 ]. The year of publication of the studies varies, with 2016 the year when more studies were published (three of them), followed by 2019, 2020, and 2021, with two studies published in each of these years.…”
Section: Resultsmentioning
confidence: 99%
“…Occupational therapy in stroke involves working with the patient, the caregiver, and the family unit. All of the interventions focused on improvements in the functional ability of the person with stroke (n = 1803), whereas the caregiver was considered an important factor in patient rehabilitation in 85% of studies (the study included, for example, the psychoeducation of the caregiver with the aim of improving knowledge, skills, and confidence) [ 43 , 44 , 45 , 46 , 48 , 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, effective nursing intervention is essential to promote the postoperative recovery of patients following laparoscopic myomectomy. The concept of rapid rehabilitation nursing is a new nursing concept [ 18 ] to control perioperative pathophysiological changes through various modalities and improve the postoperative condition of patients [ 19 ]], to reduce the physical and mental harm caused by surgery.…”
Section: Discussionmentioning
confidence: 99%